Dissociation of Intestinal and Hepatic Activities of FXR and LXRα Supports Metabolic Effects of Terminal Ileum Interposition in Rodents - Mencarelli, Andrea (American Diabetes Association, 2013)
The farnesoid X receptor (FXR) and the liver x receptors (LXRs) are bile acid–activated receptors that are highly expressed in the enterohepatic tissues. The mechanisms that support the beneficial effects of bariatric surgery are only partially defined. We have investigated the effects of ileal interposition (IT), a surgical relocation of the distal ileum into the proximal jejunum, on FXR and LXRs in rats. Seven months after surgery, blood concentrations of total bile acids, taurocholic acid, an FXR ligand, and taurohyocholic acid, an LXRα ligand, were significantly increased by IT (P < 0.05). In contrast, liver and intestinal concentrations of conjugated and nonconjugated bile acids were decreased (P < 0.05). These changes were associated with a robust induction of FXR and FXR-regulated genes in the intestine, including Fgf15, a negative regulator of bile acid synthesis. IT repressed the liver expression of glucose-6-phosphatase (G6PC) and phosphoenolpyruvate carboxykinase (Pepck), two gluconeogenetic genes, along with the expression of LXRα and its target genes sterol regulatory element-binding protein (Srebp) 1c and fatty acid synthase (Fas) in the liver. Treating IT rats with chenodeoxycholic acid ameliorated insulin signaling in the liver. Whether confirmed in human settings, these results support the association of pharmacological therapies with bariatric surgeries to exploit the selective activation of intestinal nuclear receptors.